Impact-resistant flame-retardant conveyor belt cover rubber for steel wire rope core for coal mine and preparation method thereof
By using modified nano-sea carbon black and modified aramid fibers in the covering glue of the wire rope core flame retardant conveyor belt, combined with specific vulcanization treatment, the problem of insufficient impact resistance and wear resistance in the prior art is solved, and the problem of insufficient impact resistance and wear resistance in the prior art is achieved. Higher mechanical properties and lower rolling resistance extend life and reduce energy consumption.
Patent Information
- Application Number
- CN202411679566.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The covering glue of existing wire rope core flame-retardant conveyor belts has shortcomings in impact resistance and wear resistance, and has a large rolling resistance, which affects its service life and energy consumption.
Styrene butadiene rubber and natural rubber are used as the main rubber components, and modified nano-silane carbon black and modified aramid fibers are used as reinforcement agents to combine γ-aminopropyltrimethoxysilane and bis-[γ-(tria) oxysil)propyl]tetrasulfide is modified to reduce the number of silicon hydroxyl groups on the surface of white carbon black, promote the cross-linking of white carbon black and rubber matrix, improve the mechanical properties of the covering rubber, and pass dopamine autopolymerization and silane The coupling agent chemically modifys the aramid fibers to enhance their adhesive properties with the rubber matrix.
It significantly improves the impact and wear resistance of the cover glue, while reducing rolling resistance, extending service life and reducing energy consumption.
Smart Images

Figure CN119176976A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of conveyor belt technology, and particularly relates to an impact-resistant flame-retardant cover rubber for steel wire rope core conveyor belts used in coal mines and its preparation method. Background Technology
[0002] With the development of my country's coal mining industry, its level of mechanization and automation has been continuously improving. However, due to the demands of the conveying environment, especially during coal mining, materials are not only uneven in size but also experience significant drops, resulting in substantial impact energy on the conveyor belt. Therefore, higher requirements are placed on the impact resistance of the conveyor belt. Currently produced steel cord flame-retardant conveyor belts have good flame-retardant and antistatic properties, but their cover rubber has low mechanical properties, particularly poor wear resistance and impact resistance, leading to a short service life. Furthermore, existing steel cord flame-retardant conveyor belts experience high rolling resistance and high energy consumption during use. Since the service life and energy consumption of the conveyor belt are closely related to the cover rubber, it is necessary to develop a new type of impact-resistant steel cord flame-retardant conveyor belt cover rubber for coal mines.
[0003] Chinese patent application CN104910472A discloses a high-strength, wear-resistant, and flame-retardant conveyor belt cover rubber for coal mines and its preparation method. The method involves plasticizing chloroprene rubber and butadiene rubber on an open mill, then mixing them in an internal mixer. Reinforcing fillers, vulcanizing activators, plasticizers, antioxidants, and flame retardants are added and mixed further. After re-mixing, sheeting, and cooling with a fan at room temperature, a first-stage compound rubber is obtained. The obtained first-stage compound rubber, vulcanizing agent, and vulcanization accelerator are then added to the internal mixer for mixing, followed by re-mixing, sheeting, and cooling with a fan at room temperature to obtain the final product. The cover rubber prepared by this method has good mechanical properties and wear resistance, but its rolling resistance is relatively high.
[0004] Chinese patent application CN115710389A discloses a low-rolling-resistance, high-wear-resistant steel cord core flame-retardant conveyor belt cover rubber and its preparation method. The method involves blending SiO2, ADP, AP, and nano-Si3N4. First, a SiO2 / ADP hybrid flame-retardant reinforcing material is prepared by bio-based monomer modification using GMA. Then, a SiO2 / ADP / CSM hybrid modified masterbatch is prepared by macromolecular modification using CSM. This masterbatch is then blended with 70% chlorinated paraffin, antimony trioxide, and red phosphorus to form a flame-retardant reinforcing system, and then blended with SSBR / ENR to prepare the low-rolling-resistance, high-wear-resistant steel cord core flame-retardant conveyor belt cover rubber. The cover rubber prepared by this method has low rolling resistance, but its impact resistance is poor. Summary of the Invention
[0005] In order to solve the technical problems of high rolling resistance, poor impact resistance and wear resistance of the cover rubber in related technologies, the purpose of this invention is to provide an impact-resistant flame-retardant conveyor belt cover rubber for steel wire rope core in coal mines and its preparation method.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows: Impact-resistant, flame-retardant conveyor belt cover rubber for coal mines with steel wire rope core comprises the following components and their weight proportions: Styrene-butadiene rubber 60-65 parts, natural rubber 30-40 parts, reinforcing agent 40-45 parts, flame retardant 15-20 parts, antioxidant 10-15 parts, accelerator TMTD 5-8 parts, accelerator CZ 5-8 parts, sulfur 5-10 parts. The reinforcing agent is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 11-14:4-7:2-5.
[0007] In this invention, styrene-butadiene rubber (SBR) and natural rubber are selected as the rubber matrix. SBR has a low average molecular weight, introduces large phenyl side groups on its main molecular chain, and contains ethylene side groups formed by butadiene-1,2 structures, resulting in large steric hindrance, a compact molecular structure, and superior impact resistance. Natural rubber has good mechanical properties, including good flexural fatigue resistance, high tear strength, and good abrasion and cold resistance. In this invention, modified nano-silica, modified aramid fiber, and zinc oxide are selected in a specific mass ratio to form a reinforcing agent, which is added to the rubber matrix. This effectively improves the mechanical properties of the cover rubber and reduces its rolling resistance. Zinc oxide also promotes the vulcanization process of the rubber matrix.
[0008] The modified nano-silica is prepared as follows: γ-aminopropyltrimethoxysilane is added to the nano-silica slurry, stirred thoroughly, and then spray-dried to obtain powder. The powder is heated at 200-250℃ for 1.8-2.2h, cooled, and mixed with an ethanol aqueous solution. A pH adjuster is added, the temperature is raised to 80-85℃, and then ultrasonically vibrated. Bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added, and the mixture is allowed to react fully. After aging, the mixture is filtered and washed to obtain the modified nano-silica.
[0009] The surface of silica contains a large number of silanol groups, which cause it to form agglomerates in the rubber matrix, affecting the performance of the cover rubber. In this invention, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide are used to composite modify nano-silica, reducing the number of silanol groups on the silica surface, thus weakening the surface polarity of silica, increasing the organic content, avoiding stress concentration caused by silica agglomeration, and hindering crack initiation and propagation. γ-aminopropyltrimethoxysilane can introduce amino groups into the silica surface. These amino groups act as active sites, and through further modification with bis-[γ-(triethoxysilyl)propyl]tetrasulfide, long-chain molecules are introduced into the silica surface, thereby promoting entanglement and cross-linking between silica and the rubber matrix, thus improving the mechanical properties of the cover rubber. In addition, the research found that γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide can also change the steric hindrance of the rubber chain, which can effectively reduce the rolling resistance of the cover rubber.
[0010] Furthermore, in the preparation method of modified nano-silica, the nano-silica slurry is a mixture of nano-silica and deionized water, and the mass percentage of nano-silica is 10%-13%; the mass ratio of nano-silica, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 23-27:7-10:2-5.
[0011] Furthermore, in the preparation method of modified nano-silica, the mass percentage of the ethanol aqueous solution is 85%-90%, and the amount of ethanol aqueous solution used is 3-5 times the mass of the powder; the pH adjuster is glacial acetic acid or citric acid, and the pH value of the pH adjuster added to the system is 4-5.
[0012] Furthermore, the modified aramid fiber is prepared by adding tris(hydroxymethyl)aminomethane to an aqueous solution of dopamine hydrochloride until the pH value is 8.0-8.5, adding aramid fiber, stirring and heating to 30-35°C, keeping the reaction at this temperature for 1-2 hours, then adding N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, allowing the reaction to proceed fully, centrifuging to separate the fibers, washing and drying to obtain the modified aramid fiber.
[0013] Aramid fibers possess excellent specific strength, elastic modulus, and toughness, and can char at high temperatures, making them a high-performance reinforcing fiber with flame-retardant properties. However, the smooth surface and chemical inertness of aramid fibers reduce their interfacial adhesion to rubber matrix materials. In this invention, aramid fibers are immersed in an aqueous solution of dopamine hydrochloride. Under alkaline conditions, dopamine undergoes a self-polymerization reaction, adhering to the aramid fiber surface through van der Waals forces, hydrogen bonds, and π-π stacking interactions to form a polydopamine coating. Then, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is added and grafted onto the polydopamine surface, introducing long-chain organic molecules onto the aramid fiber surface. This promotes entanglement and cross-linking between the aramid fibers and the rubber matrix, thereby improving the mechanical properties of the cover adhesive. Furthermore, the aramid fibers form a fiber network structure within the rubber matrix material, effectively enhancing the impact resistance of the cover adhesive.
[0014] Furthermore, in the method for preparing modified aramid fibers, the mass ratio of aramid fibers, dopamine hydrochloride, and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 17-21:10-13:5-9.
[0015] Furthermore, the mass percentage of the dopamine hydrochloride aqueous solution in the preparation method of modified aramid fiber is 5%-10%.
[0016] Furthermore, the flame retardant is one or more of zinc borate, aluminum hydroxide, ammonium polyphosphate, and red phosphorus.
[0017] Furthermore, the antioxidant is one or more of antioxidant RD, antioxidant 4020, antioxidant 4010NA, and microcrystalline wax.
[0018] The present invention also provides a method for preparing the impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core, comprising the following steps: S1: Add styrene-butadiene rubber and natural rubber to a two-roll mill and mix them evenly. Then add reinforcing agent, flame retardant and antioxidant. Tap the rubber until the rubber compound is evenly mixed. Then add it to a three-stage mixer, heat it to 85-90℃, and rotate the rotor at 80-85 rpm to plasticize it and obtain the rubber compound. S2: Cool the rubber compound obtained in step S1 naturally, then add accelerator TMTD, accelerator CZ and sulfur, place it on a two-roll mill and cut it in a figure-eight pattern until it is evenly mixed, then roll it into a triangular bundle four times and then sheet it to obtain the mixed rubber. S3: The vulcanization time of the compound obtained in step S2 is tested using a flat vulcanizing apparatus, and the compound is vulcanized at a temperature of 145-150℃ to obtain an impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core.
[0019] Compared with the prior art, the impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope and its preparation method provided by the present invention have the following technical advantages: (1) In this invention, modified nano-silica, modified aramid fiber and zinc oxide are selected in a certain mass ratio to form a reinforcing agent and added to the rubber matrix, which effectively improves the mechanical properties of the cover rubber and reduces the rolling resistance of the cover rubber. Zinc oxide can also promote the vulcanization process of the rubber matrix. (2) The present invention utilizes dopamine self-polymerization and silane coupling agent grafting reaction to chemically modify aramid long fibers, thereby improving the surface activity of aramid long fibers and the adhesion performance between aramid long fibers and rubber matrix, promoting the entanglement and cross-linking between aramid fibers and rubber matrix, thereby improving the mechanical properties of the cover adhesive; in addition, the aramid fibers form a fiber network structure in the rubber matrix material, which can effectively improve the impact resistance of the cover adhesive. (3) In this invention, styrene-butadiene rubber and natural rubber are selected as the rubber body. Styrene-butadiene rubber has large steric hindrance and a compact molecular structure, and has better impact resistance. Natural rubber has good mechanical properties, good flexural fatigue resistance, high tear strength, and good wear resistance and cold resistance. Attached Figure Description
[0020] Figure 1 Process flow diagram for the cover rubber of impact-resistant steel wire rope core flame-retardant conveyor belt for coal mines; Figure 2 Schematic diagram of a digital drop hammer low-speed impact testing device.
[0021] Figure 2 In the diagram, 1 is an iron plate, 2 is a guide rail, 3 is an electromagnet suction plate, 4 is an accelerometer, 5 is a force sensor, 6 is a light shield, 7 is a punch, 8 is an infrared velocimeter, 9 is a fixture, and 10 is a test piece. Detailed Implementation
[0022] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. These specific embodiments are only some embodiments of the present invention and are not intended to limit the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the protection scope of the present invention.
[0023] The process flow diagram of the impact-resistant steel wire rope core flame-retardant conveyor belt cover rubber for coal mines described in this specific embodiment is as follows: Figure 1 As shown.
[0024] Example 1 Impact-resistant, flame-retardant conveyor belt cover rubber for coal mines with steel wire rope core comprises the following components and their weight proportions: The mixture comprises 60 parts styrene-butadiene rubber, 40 parts natural rubber, 40 parts reinforcing agent, 15 parts ammonium polyphosphate, 10 parts antioxidant RD, 5 parts accelerator TMTD, 5 parts accelerator CZ, and 5 parts sulfur. The reinforcing agent is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 11:4:2.
[0025] The modified nano-silica is prepared as follows: γ-aminopropyltrimethoxysilane is added to a 10% (w / w) nano-silica slurry (the nano-silica slurry is a mixture of nano-silica and deionized water), and after thorough stirring, it is spray-dried to obtain powder. The powder is heated at 200℃ for 2.2 h, cooled, and then mixed with an 85% (w / w) ethanol aqueous solution. The amount of ethanol aqueous solution is 3 times the mass of the powder. A pH adjuster (glacial acetic acid or citric acid) is added to adjust the pH of the system to 4. After heating to 80℃, it is ultrasonically vibrated, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added. The mixture is allowed to react fully, aged, filtered, and washed to obtain modified nano-silica. The mass ratio of nano-silica, γ-aminopropyltrimethoxysilane, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 23:7:2.
[0026] The modified aramid fiber is prepared by adding tris(hydroxymethyl)aminomethane to a 5% (w / w) aqueous solution of dopamine hydrochloride until the pH value is 8.0, adding aramid fiber, stirring and heating to 30°C, and keeping the reaction at this temperature for 1 hour. Then, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is added under stirring, and the reaction is allowed to proceed fully. The mixture is then centrifuged, washed, and dried to obtain the modified aramid fiber. The mass ratio of the aramid fiber, dopamine hydrochloride, and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 17:10:5.
[0027] The preparation method of the impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core includes the following steps: S1: Add styrene-butadiene rubber and natural rubber to a two-roll mill and mix evenly. Then add reinforcing agent, ammonium polyphosphate and antioxidant RD. Tap the rubber until the rubber compound is evenly mixed. Then add it to a three-component mixer, heat it to 85°C, and rotate the rotor at 80 rpm to plasticize it and obtain the rubber compound. S2: Cool the rubber compound obtained in step S1 naturally, then add accelerator TMTD, accelerator CZ and sulfur, place it on a two-roll mill and cut it in a figure-eight pattern until it is evenly mixed, then roll it into a triangular bundle four times and then sheet it to obtain the mixed rubber. S3: The vulcanization time of the compound obtained in step S2 is tested using a flat vulcanizing apparatus, and the compound is vulcanized at a temperature of 145℃ to obtain an impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core.
[0028] Example 2 Impact-resistant, flame-retardant conveyor belt cover rubber for coal mines with steel wire rope core comprises the following components and their weight proportions: The composition includes 65 parts styrene-butadiene rubber, 30 parts natural rubber, 45 parts reinforcing agent, 20 parts zinc borate, 15 parts antioxidant 4020, 8 parts accelerator TMTD, 8 parts accelerator CZ, and 10 parts sulfur. The reinforcing agent is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 14:7:5.
[0029] The modified nano-silica is prepared as follows: γ-aminopropyltrimethoxysilane is added to a 13% (w / w) nano-silica slurry (the nano-silica slurry is a mixture of nano-silica and deionized water), and after thorough stirring, it is spray-dried to obtain powder. The powder is heated at 250°C for 2.2 hours, cooled, and then mixed with a 90% (w / w) ethanol aqueous solution. The amount of ethanol aqueous solution is 5 times the mass of the powder. A pH adjuster (glacial acetic acid or citric acid) is added to adjust the pH of the system to 5. After heating to 85°C, the mixture is ultrasonically vibrated, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added. The mixture is allowed to react fully, aged, filtered, and washed to obtain modified nano-silica. The mass ratio of nano-silica, γ-aminopropyltrimethoxysilane, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 27:10:5.
[0030] The modified aramid fiber is prepared by adding tris(hydroxymethyl)aminomethane to a 10% (w / w) aqueous solution of dopamine hydrochloride until the pH value reaches 8.5, adding aramid fiber, stirring and heating to 35°C, and maintaining the temperature for 2 hours. Then, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is added under stirring, and the reaction is allowed to proceed fully. The mixture is then centrifuged, washed, and dried to obtain the modified aramid fiber. The mass ratio of the aramid fiber, dopamine hydrochloride, and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 21:13:9.
[0031] The preparation method of the impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core includes the following steps: S1: Add styrene-butadiene rubber and natural rubber to a two-roll mill and mix them evenly. Then add reinforcing agent, zinc borate and antioxidant 4020. Tap the rubber until the rubber compound is evenly mixed. Then add it to a three-stage mixer, heat it to 90°C, and rotate the rotor at 85 rpm to plasticize it and obtain the rubber compound. S2: Cool the rubber compound obtained in step S1 naturally, then add accelerator TMTD, accelerator CZ and sulfur, place it on a two-roll mill and cut it in a figure-eight pattern until it is evenly mixed, then roll it into a triangular bundle four times and then sheet it to obtain the mixed rubber. S3: The vulcanization time of the compound obtained in step S2 is tested using a flat vulcanizing apparatus, and the compound is vulcanized at a temperature of 150℃ to obtain an impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core.
[0032] Example 3 Impact-resistant, flame-retardant conveyor belt cover rubber for coal mines with steel wire rope core comprises the following components and their weight proportions: The composition includes 63 parts styrene-butadiene rubber, 37 parts natural rubber, 42 parts reinforcing agent, 18 parts red phosphorus, 13 parts antioxidant 4010NA, 7 parts accelerator TMTD, 7 parts accelerator CZ, and 8 parts sulfur. The reinforcing agent is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 13:6:4.
[0033] The modified nano-silica is prepared as follows: γ-aminopropyltrimethoxysilane is added to a 12% (w / w) nano-silica slurry (the nano-silica slurry is a mixture of nano-silica and deionized water), and after thorough stirring, it is spray-dried to obtain powder. The powder is heated at 230℃ for 2.0 h, cooled, and then mixed with an 88% (w / w) ethanol aqueous solution. The amount of ethanol aqueous solution is 4 times the mass of the powder. A pH adjuster (glacial acetic acid or citric acid) is added to adjust the pH of the system to 4.5. After heating to 83℃, the mixture is ultrasonically vibrated, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added. The mixture is allowed to react fully, aged, filtered, and washed to obtain modified nano-silica. The mass ratio of nano-silica, γ-aminopropyltrimethoxysilane, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 25:9:4.
[0034] Furthermore, the modified aramid fiber is prepared by adding tris(hydroxymethyl)aminomethane to an 8% (w / w) aqueous solution of dopamine hydrochloride until the pH value is 8.3, adding aramid fiber, stirring and heating to 32°C, and maintaining the temperature for 1.5 h, then adding N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, reacting fully, centrifuging, washing and drying to obtain the modified aramid fiber; the mass ratio of the aramid fiber, dopamine hydrochloride and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 19:12:7.
[0035] The preparation method of the impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core includes the following steps: S1: Add styrene-butadiene rubber and natural rubber to a two-roll mill and mix them evenly. Then add reinforcing agent, red phosphorus and antioxidant 4010NA. Tap the rubber until the rubber compound is evenly mixed. Then add it to a three-stage mixer, heat it to 87°C, and rotate the rotor at 83 rpm to plasticize it and obtain the rubber compound. S2: Cool the rubber compound obtained in step S1 naturally, then add accelerator TMTD, accelerator CZ and sulfur, place it on a two-roll mill and cut it in a figure-eight pattern until it is evenly mixed, then roll it into a triangular bundle four times and then sheet it to obtain the mixed rubber. S3: The vulcanization time of the compound obtained in step S2 is tested using a flat vulcanizing apparatus, and the compound is vulcanized at a temperature of 148℃ to obtain an impact-resistant flame-retardant conveyor belt cover rubber for coal mine steel wire rope core.
[0036] Comparative Example 1 The formulation and preparation method of the cover adhesive described in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that the reinforcing agent described in this comparative example is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 1:7:10.
[0037] Comparative Example 2 The formulation and preparation method of the cover adhesive described in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of nano-silica is used in this comparative example to replace the modified nano-silica in the reinforcing agent.
[0038] Comparative Example 3 The formulation and preparation method of the cover adhesive described in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of γ-aminopropyltriethoxysilane is used instead of γ-aminopropyltrimethoxysilane in the preparation method of the modified nano-silica in this comparative example.
[0039] Comparative Example 4 The formulation and preparation method of the cover adhesive described in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that in the preparation method of the modified nano-silica in this comparative example, an equal amount of γ-methacryloxypropyltrimethoxysilane is used instead of bis-[γ-(triethoxysilyl)propyl]tetrasulfide.
[0040] Comparative Example 5 The formulation and preparation method of the cover adhesive described in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that a pH adjuster is added to adjust the pH value of the modified nano-silica in this comparative example to 6.5.
[0041] Comparative Example 6 The formulation and preparation method of the cover adhesive described in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that in the preparation method of the modified aramid fiber in this comparative example, an equal amount of deionized water is used instead of the hydrochloric acid dopamine aqueous solution.
[0042] Comparative Example 7 The formulation and preparation method of the cover adhesive described in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that an equal amount of γ-aminopropyltriethoxysilane is used instead of N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane in the preparation method of the modified aramid fiber in this comparative example.
[0043] Test case Mechanical property testing: The covering rubbers prepared in Examples 1-3 and Comparative Examples 1-7 were tested for tensile strength and elongation at break according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; the tear strength was tested according to GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)"; the tear test used right-angled tear specimens. Impact resistance testing: The impact resistance of the cover adhesives prepared in Examples 1-3 was tested using a digital drop hammer low-speed impact testing device, as described above. Figure 2 As shown, the impact load when the cover adhesive was punctured was recorded during the test; The abrasion resistance test was conducted on the cover rubbers prepared in Examples 1-3 and Comparative Examples 1-7 according to GB / T 1689-2014 "Determination of abrasion resistance of vulcanized rubber", and the abrasion volume was recorded. Rolling resistance test: The dynamic mechanical properties of the cover adhesives prepared in Examples 1-3 and Comparative Examples 1-7 were determined using a viscoelastic analyzer. The tan(δ) value at 60°C was recorded during the temperature scan under dynamic strain conditions at a frequency of 10 Hz. The experimental results are shown in Table 1.
[0044] Table 1 Performance Test Results
[0045] As shown in Table 1, the tensile strength of the impact-resistant flame-retardant conveyor belt cover rubber for coal mines provided by this invention is 21.3-24.1 MPa, the elongation at break is 439.7%-502.4%, the tear strength is 51.4-53.2 KN / m, the impact load at breakdown is 11587.6-13264.2 N, and the abrasion volume is 43-54 mm. 3 The rolling resistance is 0.099-0.123, indicating that the impact-resistant flame-retardant conveyor belt cover rubber for coal mines provided by this invention has good mechanical properties, wear resistance, and impact resistance. Among them, the impact-resistant flame-retardant conveyor belt cover rubber for coal mines prepared in Example 3 has the best performance in all aspects and is the best embodiment of this invention.
[0046] Compared with Example 3, Comparative Example 1 changed the mass ratio of each component of the reinforcing agent, but the mechanical properties of the resulting cover rubber deteriorated and the rolling resistance increased. This indicates that the amount of each component in the reinforcing agent in this invention has been optimized. Comparative Example 2 used an equal amount of nano-silica to replace the modified nano-silica in the reinforcing agent, but the mechanical properties of the resulting cover rubber deteriorated and the rolling resistance increased. This indicates that the composite modification of nano-silica with γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide in this invention can promote the entanglement and crosslinking between silica and the rubber matrix, thereby improving the mechanical properties of the cover rubber and effectively reducing the rolling resistance of the cover rubber. Comparative Example 3 used an equal amount of γ-aminopropyltriethoxysilane to replace γ-aminopropyltrimethoxysilane, but the mechanical properties of the resulting cover rubber deteriorated and the rolling resistance increased. This indicates that γ-aminopropyltrimethoxysilane can introduce amino groups on the surface of silica, which is the key to modifying nano-silica. Comparative Example 4 used an equal amount of Replacing bis-[γ-(triethoxysilyl)propyl]tetrasulfide with γ-methacryloxypropyltrimethoxysilane in Comparative Example 5, while altering the pH of the reaction system, resulted in a deterioration in the mechanical properties of the prepared cover rubber and an increase in rolling resistance. This indicates that under acidic conditions, bis-[γ-(triethoxysilyl)propyl]tetrasulfide can introduce long-chain molecules onto the surface of silica, thereby promoting the entanglement and crosslinking between silica and the rubber matrix, thus improving the mechanical properties of the cover rubber. [3-propyl]tetrasulfide and γ-aminopropyltrimethoxysilane can work together to reduce the rolling resistance of the cover rubber. In Comparative Example 6, an equal amount of deionized water was used instead of hydrochloric acid dopamine aqueous solution, and in Comparative Example 7, an equal amount of γ-aminopropyltriethoxysilane was used instead of N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane. However, the mechanical properties of the resulting cover rubber deteriorated, and the impact load at breakdown decreased. This was due to the poor modification effect of aramid fibers and their poor dispersion performance in rubber.
[0047] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the invention. Those skilled in the art should not modify the above embodiments without departing from the spirit and scope of the present invention. Therefore, any modifications, equivalent substitutions, and improvements made by those skilled in the art under the technical concept of the present invention are still covered by the claims of the present invention.
Claims
1. Impact-resistant flame-retardant steel wire rope conveyor belt covering rubber for coal mines, characterized in that: It includes the following components and their weight parts: 60-65 parts of styrene-butadiene rubber, 30-40 parts of natural rubber, 40-45 parts of reinforcing agent, 15-20 parts of flame retardant, 10-15 parts of antioxidant, 5-8 parts of accelerator TMTD, 5-8 parts of accelerator CZ, 5-10 parts of sulfur; The reinforcing agent is composed of modified nano-white carbon black, modified aramid fiber, and zinc oxide in a mass ratio of 11-14:4-7:2-5; The preparation method of the modified nano-silica is as follows: γ-aminopropyltrimethoxysilane is added to a nano-silica slurry, the powder is fully stirred and then spray-dried to obtain a powder, the powder is heated at 200-250° C. for 1.8-2.2 hours, the powder is cooled and then mixed with an ethanol aqueous solution, a pH regulator is added, the temperature is raised to 80-85° C. and then ultrasonically shaken, bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added, the powder is fully reacted, aged, filtered, washed, and the modified nano-silica is obtained.
2. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 1 is characterized in that: The nano-silica slurry is a mixture of nano-silica and deionized water, wherein the mass percentage of the nano-silica is 10%-13%; the mass ratio of the nano-silica, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 23-27:7-10:2-5.
3. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel wire rope according to claim 1 is characterized in that: The mass percentage of the ethanol aqueous solution is 85%-90%, and the amount of the ethanol aqueous solution is 3-5 times the mass of the powder; the pH adjuster is glacial acetic acid or citric acid, and the pH value of the pH adjuster added to the system is 4-5.
4. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 1 is characterized in that: The preparation method of the modified aramid fiber is as follows: add trihydroxymethylaminomethane to a dopamine hydrochloride aqueous solution until the pH value is 8.0-8.5, add aramid fiber, stir and heat to 30-35° C., keep warm for reaction for 1-2 hours, then add N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, fully react, centrifuge, wash and dry to obtain the modified aramid fiber.
5. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 4 is characterized in that: The mass ratio of the aramid fiber, dopamine hydrochloride and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 17-21:10-13:5-9.
6. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 4 is characterized in that: The mass percentage of the dopamine hydrochloride aqueous solution is 5%-10%.
7. The impact-resistant flame-retardant conveyor belt covering rubber for coal mines according to claim 1 is characterized in that: The flame retardant is one or more of zinc borate, aluminum hydroxide, ammonium polyphosphate and red phosphorus.
8. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 1 is characterized in that: The antioxidant is one or more of antioxidant RD, antioxidant 4020, antioxidant 4010NA, and microcrystalline wax.
9. The method for preparing the impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Add styrene-butadiene rubber and natural rubber to an open mixer and mix them evenly, then add a reinforcing agent, a flame retardant and an antioxidant, tap the rubber until the rubber is evenly mixed, then add the rubber to an internal mixer, heat it to 85-90°C, rotate the rotor at 80-85rpm, and perform plasticizing to obtain a rubber compound; S2: The rubber material obtained in step S1 is naturally cooled, and then accelerator TMTD, accelerator CZ and sulfur are added, and the rubber material is placed on a double-roll open mill for eight-shaped cutting until the mixing is uniform, and the rubber material is cut into sheets after four triangle packing to obtain a mixed rubber; S3: The vulcanization time of the rubber compound obtained in step S2 is tested by a flat vulcanizer, and the rubber compound is vulcanized at a vulcanization temperature of 145-150° C. to obtain an impact-resistant flame-retardant conveyor belt covering rubber for a coal mine steel wire rope core.
Citation Information
Patent Citations
Packing leather cup rubber for brake wheel cylinder of automobile and preparation method thereof
CN103102526A
Nanocomposite prepared from solution polymerized styrene-butadiene rubber highly filled with white carbon black
CN105524318A
Low rolling resistance boron carbide rubber composition and preparation process thereof
CN105542261A
Surface modification method for aramid fibers
CN107299530A
Cold-resistant and heat-resistant conveyor belt and preparation process thereof
CN109749153A
Cited By
A multi-component synergistic high-performance natural rubber sheet and its industrial preparation method
CN119735868A
Flame-retardant heat-resistant conveying belt and preparation method thereof
CN120757930A
